Community-led approaches to the academic development of pracademics in universities: evidence from Ghana - Owusu-Agyeman, Y.; Amoakohene, G. (International Journal for Academic Development, 2024)
This paper examines how pracademics who teach at different universities in Ghana contribute to shaping their academic develop ment. In this study, a pracademic refers to an industry practitioner who is employed by a university as a part-time academic to teach academic courses and support the knowledge and skills development of learners. Using a dialogical narrative approach, data were gathered from 14 pracademics who teach academic courses at different universities in Ghana. The findings revealed that the academic development of pracademics is linked to their unique professional identity, the social networks that support their personal and professional growth, and the complex professional community in which they operate. The narratives of the participants revealed that the network of pracademics serves to promote their common interests, which include needs (social, job-related, and resources), expectations, access to opportunities, and their ability to promote academic disciplines. Additionally, pracademics are likely to be highly motivated to join informal networks within a broad context – pracademia, when they know that issues concerning their job security and professional development in the areas of teaching, research, and engaged scholarship will be prioritised by the management of universities.
Research Article
Keywords: Academic development; pracademics; higher education